Speech and Language Development, Cognitive Ability and Literacy Skills in Children Identified with Learning Disabilities: A Comparative Study - Smitha Desai; Chandralata Sharma; Kritika Nair (Journal of All India Institute of Speech and Hearing, 1970)
The purpose of this study is to explore the links between speech & language development, cognitive ability and literacy skills (reading and written language) of students identified with Learning Disabilities (dyslexia). A group of 30 children with Learning Disabilities, aged 8-12 years, with a history of Speech and Language Difficulties (delay/impairments) (SLD) were compared on measures of Word Reading, Reading Comprehension and Writing skills with a group of 30 children with Learning Disabilities but with no history of Speech and Language Difficulties (delay/impairments) (nSLD). Results indicated that the mean standard scores of the SLD group were lower than the nSLD group across the test measures of Verbal IQ, Performance IQ, Global IQ and Word reading. The t-test showed significant differences between the two groups on the PIQ & GIQ (p<0.05). No significant difference was seen between the two groups on the measures of word reading, reading comprehension and writing skills. These findingshave valuable implications for planning intervention programs for children with speechand language difficulties and learning disabilities.